Pro Core Data for iOS Data Access and Persistence Engine for iPhone, iPad, and iPod touch - Privat, Michael; Warner, Robert (Apress : Imprint: Apress, 2011)
The power of Core Data allows iOS developers to efficiently store and retrieve application data using familiar object-oriented paradigms. Pro Core Data for iOS explains both how and why to use Core Data for data storage, from simple to advanced techniques. Covering common and advanced persistence patterns, this book prepares any iOS developer to store and retrieve data accurately and proficiently. Lots of iOS development books touch on Core Data, taking you through a few mainstream use cases for storing and retrieving data in your iOS applications. In Pro Core Data for iOS, however, we take you further into Core Data and show you how to leverage the power of this data framework. After reading this book, you'll be able to answer all of these questions: What are all the parts of Core Data, and how do they interact? How do I create my own custom store? Should I use plain NSManagedObject instances or custom classes? How do I undo and redo Core Data actions? How do I filter, sort, and aggregate data? What is "faulting," and why should I care? Suppose I want to change my data model; how do I migrate my users' data? Pro Core Data for iOS delves into these and other Core Data questions. With explanations, diagrams, code samples, and working explanations, this book will make you a Core Data pro!